The Influence of Organizational Culture, Work Discipline And Compensation Toward Employee Performance At PT. Jasa Marga - Syahirah Ishmah Hutabarat; Kiki Farida Ferine; Henry Aspan (Britain International for Academic Research (BIAR) Publisher, 2022)
This research was conducted to explain the partial or simultaneous influence of the variables of organizational culture, work discipline and compensation on the performance of employees at PT. JASA MARGA. The total population used is 78 respondents, employees who work at PT. JASA MARGA which was taken using a questionnaire as a data collection method in this study. This study uses multiple linear regression analysis. The results of the analysis show that there is a simultaneous significant effect between the three variables, and a partially significant influence between the organizational culture, work discipline and compensation variables on the performance of employees at PT. Jasa Marga.